2014
DOI: 10.1177/0883073814542946
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Disease Progression in Giant Axonal Neuropathy

Abstract: As part of a natural history study of giant axonal neuropathy, we hypothesized that the Friedreich Ataxia Rating Scale and the Gross Motor Function Measure would show a significant change over 6 months, reflecting subjects' decline in motor function. The Friedreich Ataxia Rating Scale was performed on 11 subjects and the Gross Motor Function Measure was performed on 10 subjects twice with a six-month interval. A paired two-tailed t-test was used to assess the difference in each subject's score. Significant cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…These IF inclusion bodies in lens epithelial cells appear to be unique to GAN, as similar IF inclusion bodies have not been reported previously in experimental animal models or human diseases. Although lens abnormalities have not been reported in clinical or postmortem studies of human GAN [1216], we confirmed in a specimen obtained at autopsy that similar appearing, intracytoplasmic inclusion bodies are also present in lens epithelial cells in human GAN (Fig. 2e).…”
supporting
confidence: 75%
“…These IF inclusion bodies in lens epithelial cells appear to be unique to GAN, as similar IF inclusion bodies have not been reported previously in experimental animal models or human diseases. Although lens abnormalities have not been reported in clinical or postmortem studies of human GAN [1216], we confirmed in a specimen obtained at autopsy that similar appearing, intracytoplasmic inclusion bodies are also present in lens epithelial cells in human GAN (Fig. 2e).…”
supporting
confidence: 75%
“…Such observations extend the pathologic characterization of the GAN KO mouse model and may provide an explanation for symptoms suggestive of ANS dysfunction in GAN patients. Further investigation of ANS dysfunction in human GAN may be warranted to (1) augment standardized, clinically meaningful measurements for the rate of unmitigated disease progression in natural history studies [13], (2) promote continued development of alternative outcome measures for therapeutic effect in clinical trials, and (3) expand quality of life (QoL) metrics for GAN patients and their families [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Progressive distal motor weakness is the initial symptom in all cases. Diffused muscle atrophy, most predominantly in distal muscles, flaccid, paralysis, severely decreased muscle strength, low muscle tone, and loss of reflexes (areflexia) may be observed as the disease advances ( Table 2 ) [ 3 , 22 , 23 , 24 , 25 , 26 , 37 , 38 ]. Diagnosis of PNS degeneration in early infancy and sensorimotor pathway involvement in teens resemble more commonly inherited peripheral neuropathy called Charcot-Marie-Tooth (CMT) diseases [ 27 ].…”
Section: Clinical Heterogeneity In Persons With Ganmentioning
confidence: 99%
“…Diagnosis of PNS degeneration in early infancy and sensorimotor pathway involvement in teens resemble more commonly inherited peripheral neuropathy called Charcot-Marie-Tooth (CMT) diseases [ 27 ]. Owing to similarities in clinical presentation between patients with GAN and CMT or Friedreich ataxia, CTM Disease Pediatric Scale and Friedreich Ataxia Rating Scale and Gross Motor Function measure may be implemented for physical examination [ 4 , 37 ]. Though, making PNS deterioration unique from some of the other peripheral neuropathies, GAN also leads to proximal motor weakness, evidenced by pectoralis chest-wall muscle wasting, winged scapula, and exhibition of myopathic or “waddling” gait disturbances and positive Gower’s sign during the attempt to achieve erect position, indicative of pelvic girdle and quadriceps muscle weakness [ 2 , 4 , 6 , 25 , 28 ].…”
Section: Clinical Heterogeneity In Persons With Ganmentioning
confidence: 99%
See 1 more Smart Citation